Magnetic model and heterogeneity of the crystalline crust of the southwestern boundary of the East European Сraton - Pashkevich, I.K.; Orlyuk, M.I.; Bakarzhieva, M.I.; Marchenko, A.V. (Geofizicheskiy Zhurnal, 2025)
The paper presents 3D magnetic modeling of the crystalline crust in the Teissere-Tornquist line (TTL) area and its northwestern branching into the Sorgenfrei and Thor-Tornquist zones. The anomalous magnetic field was analyzed based on ground, airborne, and satellite surveys. The boundaries of the East European Craton segments follow the structure of the TTL, in which we have identified two branches of different strikes; they form a triple articulation with the Fennoscandia-Sarmatia suture zone.The TTL segmentation corresponds to the distribution of magnetic sources along the TTL.